On the Identity, Nomenclature, Flowering and Utility of the Climbing Bamboo Melocalamus compactiflorus - Bahadur, K. N.; Naithani, H. B. (Indian Forester, 1983)
Melocalamus compactiflorus is a handsome bamboo characterised by its c1imbing habit and large fleshy seeds. Commonly distributed in Bangladesh, Burma and Yunnan (China). It is known from the wild in India only from Cachar (Assam). It was erroneously transferred to the Dinochloa by McClure in 1937. After examining the authentic material this mistake has been rectified; some misidentifications have also been corrected. Although published records of the flowering of this bamboo from Burma are available, such a record from India was so far lacking. A population of this bamboo at F.R.I., Dehra Dun flowered in late 1980 which now forms the basis of this record. As per the available data the flowering cycle in this species seems to vary between 7 and 47 years. Shoes/sandals are made of the outer green fibrous layers of the culms of this climbing bamboo.